Исследование баланса реактивности и эффективности органов СУЗ при проведение физического пуска реактора ИВГ.1М с НОУ топливом - Прозорова И. В. (2023, 2023)
The IVG.1M research reactor (Kurchatov, Kazakhstan) was converted to low-uranium enriched (LEU) fuel in accordance with the nuclear non-proliferation programme. In order to determine and control the characteristics of the reactor with LEU fuel, experimental studies were conducted during the physical start-up of the reactor. This paper presents the main research results of the reactor characteristics after fuel conversion.